On the Regge behaviour of the AdS Virasoro-Shapiro amplitude - Luis F. Alday; Maria Nocchi; Clément Virally; Xinan Zhou (Journal of High Energy Physics)
Abstract We compute the AdS Virasoro-Shapiro amplitude in the Regge limit, in terms of the CFT data of the exchanged operators in the leading Regge trajectory. To any order in the small curvature expansion, the result can be written in terms of derivatives of the flat space Virasoro-Shapiro amplitude in the Regge limit. The result also admits an integral representation involving single-valued logarithms, fully consistent with recent proposals for the full AdS Virasoro-Shapiro amplitude.